Biology and integrated pest management for the banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) - Gold, Cliford S.; Pena, J.E.; Karamura, E.B. (2001)
The banana weevil Cosmopolites sordidus (Germar) is the most important insect pest of bananas and plantains (Musa spp.). The larvae bore in the corm, reducing nutrient uptake and weakening the stability of the plant. Attack in newly planted banana stands can lead to crop failure. In established fields, weevil damage can result in reduced bunch weights, mat die-out and shortened stand life. Damage and yield losses tend to increase with time. This paper reviews the research on the taxonomy, distribution, biology, pest status, sampling methods, and integrated pest management (IPM) of banana weevil. Salient features of the weevil's biology include nocturnal activity, long life span, limited mobility, low fecundity, and slow population growth. The adults are free living and most often associated with banana mats and cut residues. They are attracted to their hosts by volatiles, especially following damage to the plant corm. Males produce an aggregation pheromone that is attractive to both sexes. Eggs are laid in the corm or lower pseudostem. The immature stages are all passed within the host plant, mostly in the corm. The weevil's biology creates sampling problems and makes its control difficult. Most commonly, weevils are monitored by trapping adults, mark and recapture methods and damage assessment to harvested or dead plants. Weevil pest status and control options reflect the type of banana being grown and the production system. Plantains and highland bananas are more susceptible to the weevil than dessert or brewing bananas. Banana production systems range from kitchen gardens and small, low-input stands to large-scale export plantations. IPM options for banana weevils include habitat management (cultural controls), biological control, host plant resistance, botanicals, and (in some cases) chemical control. Cultural controls have been widely recommended but data demonstrating their efficacy are limited. The most important are clean planting material in new stands, crop sanitation (especially destruction of residues), agronomic methods to improve plant vigour and tolerance to weevil attack and, possibly, trapping. Tissue culture plantlets, where available, assure the farmer with weevil-free material. Suckers may be cleaned by paring, hot water treatment and/or the applications of entomopathogens, neem, or pesticides. None of these methods assure elimination of weevils. Adult weevils may also invade from nearby plantations. As a result, the benefits of clean planting material may be limited to a few crop cycles. Field surveys suggest that reduced weevil populations may be associated with high levels of crop sanitation, yet definitive studies on residue management and weevil pest status are wanting. Trapping of adult weevils with pseudostem or corm traps can reduce weevil populations, but material and labour requirements may be beyond the resources of many farmers. The use of enhanced trapping with pheromones and kairomones is currently under study. A combination of clean planting material, sanitation, and trapping is likely to provide at least partial control of banana weevil. Classical biological control of banana weevil, using natural enemies from Asia, has so far been unsuccessful. Most known arthropod natural enemies are opportunistic, generalist predators with limited efficacy. Myrmicine ants have been reported to help control the weevil in Cuba, but their effects elsewhere are unknown. Microbial control, using entomopathogenic fungi and nematodes tend to be more promising. Effective strains of microbial agents are known but economic mass production and delivery systems need further development. Host plant resistance offers another promising avenue of control. Numerous resistant clones are known, including Yangambi-km 5, Calcutta 4, and Pisang awak. Resistance is most often through antibiosis resulting in egg or larval failure. Banana breeding is a slow and difficult process. Current research is exploring genetic improvement through biotechnology techniques including the introduction of foreign genes. Neem has also shown potential for control of banana weevil. Studies on the use of other botanicals against banana weevil have failed to produce positive results. Chemical control of banana weevil remains a common and effective method for larger scale producers but is beyond the reach of resource-poor farmers. However, the weevil has displayed the ability to develop resistance against a broad range of chemicals. In summary, cultural control remains the most available approach for resource-poor farmers. A combination of several cultural methods is likely to reduce weevil pressure. Among the methods currently under study, microbial control, host plant resistance and neem appear to offer the most promise.